ORIGINAL ARTICLE: A COMPREHENSIVE STUDY OF PROSTATIC LESIONS AND ITS PROSTATE-SPECIFIC ANTIGEN LEVELS IN ANATOMICAL PATHOLOGY INSTALLATION OF RSUD DR. SOETOMO, SURABAYA FROM YEAR 2014 TO 2016 - Izzan Khalidah Binti Muhamad; Anny Setijo Rahaju; Lukman Hakim (Jurnal Kedokteran Syiah Kuala, 2019)
Abstract. Background: Diseases primarily affects prostate gland are inflammation, hyperplasia, and malignant tumour. Gleason score (GS) is an essential facet and together with PSA are substantial in diagnosing, managing, and determining the prognosis of CaP. Purpose: The aims of this study is to investigate the prevalence of prostatic lesions and its PSA level among patients in anatomical pathology installation in RSUD Dr. Soetomo from year 2014 to 2016. Method: This research is a retrospective study of prostatic lesions that were conducted from year 2014 to 2016 (3 years) with emphasis on GS and PSA levels. Result: The distribution of histopathological lesion found are benign lesion, benign prostate hyperplasia, adenocarcinoma, prostatitis, benign prostate hyperplasia with prostatitis, prostatic intraepithelial neoplasia, non-Hodgkin lymphoma, sarcoma, transitional cell carcinoma, and squamous cell carcinoma. The most common findings in this cohort is benign lesion (34.6%) with age group of 61-70 years old (51.94%) and adenocarcinoma with high GS of 9 (60%). Meanwhile, patients with GS 8 (high risk patient) contributed for 84.8%. Most of the cases (69.2%) have elevated PSA level of 20 ng/ml. Conclusion: The prevalence of prostatic lesions were able to be determined in different age groups. High GS indicates a more aggressive type of adenocarcinoma suffered, high risk for CaP.  The results show that the possibility to detect malignancy with rising PSA level are higher, although PSA is not considered as a specific marker.Keywords: prostate, histopathology, benign lesion, PSA.